In Situ Preservation Fraction of Parathyroid Gland in Thyroidectomy: A Cohort Retrospective Study - Han Luo; Wanjun Zhao; Hongliu Yang; Anping Su; Bin Wang; Jingqiang Zhu (International Journal of Endocrinology)
Background and Objectives. Parathyroid failure is the most common symptom after thyroidectomy. To prevent it, a gland was preserved in situ or an ischemic one was autotransplanted. This study explored the relationship between in situ preservation of the parathyroid gland and gland failure. Methods. Consecutive patients who underwent initial total thyroidectomy were enrolled retrospectively in a prospectively maintained database. Patients were divided into groups by parathyroid gland remaining in situ fraction (PGRIF) (PGRIF = number of in situ glands/(total number of identified glands − number of glands in specimen). Patients were graded by tertiles and followed at least one year after surgery. Results. 559 patients were included. PGRIF is significantly inversely associated with transient hypoparathyroidism, protracted hypoparathyroidism, and postoperative hypocalcemia. PGRIF was identified as an independent risk factor for transient hypoparathyroidism, protracted hypoparathyroidism, and postoperative hypocalcemia (OR=0.177, 0.190, and 0.330, resp.). Autotransplantation of parathyroid gland would not affect the calcium level in the long term. Conclusion. In situ preservation of parathyroid gland is crucial for parathyroid function. Less preserved is the independent risk factor for postoperative hypoparathyroidism and hypocalcemia, resulting in a worse function of parathyroid gland in the long term.